Endothelium capture‐based liver segment imaging using vascular endothelial growth factor receptor 2 in preclinical ex vivo models - Kyuno, Daisuke; Qian, Baifeng; Gross, Wolfgang; Schäfer, Michael; Ryschich, Eduard (BJS open, 2020)
Imaging of liver segments provides substantial information for surgeons when performing liver resection. The anti‐vascular endothelial growth factor receptor (VEGFR) 2 antibody ramucirumab conjugated...